Outcomes of axicabtagene ciloleucel in PMBCL compare favorably with those in DLBCL: a GLA/DRST registry study - Schubert, Maria-Luisa; Bethge, Wolfgang A.; Ayuk, Francis A.; von Bonin, Malte; Vucinic, Vladan; Wagner-Drouet, Eva Marie; Subklewe, Marion; Baldus, Claudia D.; Glass, Bertram; Marks, Reinhard; Mougiakakos, Dimitrios; Schroers, Roland; et al. (Blood advances, 2023)
TO THE EDITOR:Primary mediastinal B-cell lymphoma (PMBCL) is an aggressive large B-cell lymphoma (LBCL) of thymic origin occurring predominantly in young patients and accounting for 2% to 4% of non-Hodgkin lymphomas.1,2 Anti-CD19 chimeric antigen receptor T cells (CARTs) have been adopted as standard of care for the treatment of patients with relapsed and/or refractory (r/r) LBCL, including PMBCL beyond second treatment line.3,4 Axicabtagene ciloleucel (axi-cel) has been the first CART therapy specifically approved for treatment of PMBCL in this setting. However, because of the rarity of the disease, information on safety and efficacy of CARTs in PMBCL is limited.5-7 Here, we compared course and outcome of axi-cel-treatment in patients with r/r PMBCL and those with r/r diffuse LBCL (DLBCL), not otherwise specified.
Gesehen am 31.01.2024